Slum imaginaries and spatial justice in Philippine cinema - Macapagal, Katrina (Edinburgh University Press, 2021)
Outlining the rise of Philippine slums alongside the historical development of Philippine urban cinema, Slum Imaginaries and Spatial Justice in Philippine Cinema makes a novel contribution to the cinema-city nexus through its interdisciplinary framework of film studies and human geography.